Monitoring pulmonary health in Swiss childhood cancer survivors. Issue 10 (15th June 2018) - Kasteler, Rahel; Kam, Linda M. H.; Weiss, Annette; Waespe, Nicolas; Sommer, Grit; Singer, Florian; von der Weid, Nicolas X.; Ansari, Marc; Kuehni, Claudia E.; ,
Abstract: Background: Childhood cancer survivors are at increased risk for pulmonary morbidity and mortality. International guidelines recommend pulmonary function tests (PFT) during follow‐up care. This nationwide study assessed how many children received PFT within 5 years after pulmotoxic treatment in Switzerland, types of tests, and predictors for testing. Methods: We included all children from the Swiss Childhood Cancer Registry who were diagnosed with cancer from 1990 to 2013 at age 0–16 years, survived for ≥2 years from diagnosis, and had pulmotoxic chemotherapy with bleomycin, busulfan, nitrosoureas, and/or chest radiotherapy. We searched medical records in all Swiss pediatric oncology clinics for PFT (spirometry, plethysmography, diffusion capacity of carbon monoxide [DLCO]) and treatment details. Results: We found medical records for 372 children, of whom 147 had pulmotoxic chemotherapy and 323 chest radiotherapy. Only 185 had plethysmography and/or spirometry (50%), 122 had DLCO (33%). Testing varied by cancer center from 3% to 79% ( P  = 0.001). Central nervous system tumor survivors and those not treated according to study protocols had less plethysmography and/or spirometry (odds ratio (OR) 0.3 and 0.3), lymphoma survivors and those who were symptomatic had more PFT (plethysmography and/or spirometry: OR 5.9 and 8.7; DLCO: OR 3.4 and 2.3). Cumulative incidence (CuI) of PFT was 52% in the first 5 years after pulmotoxic treatment; most of the tests were done in the first 2 years after treatment (CuI 44%). Conclusion: Only half of the survivors exposed to pulmotoxic treatment have been followed up with PFT in Switzerland. We need to optimize, update, and implement monitoring guidelines.